Teaching Strategies to Cope High School Students with Special Needs in EFL Class - Khofifah, Mutiara; Anugerahwati, Mirjam (Makassar State University, 2024)
Abstract. This study was conducted to investigate how students with special needs in a private school learn an English subject as a foreign language and to explore the English teaching strategies that are utilized by teachers at the secondary level. This study collected quantitative data from 3 teachers at Panjura Private School, Malang. This study used a case study in which the data collected from the interview guide and classroom observation checklist as the instruments to know the technique, challenges, and how the teachers solve the problem that comes from the challenges. The findings revealed that the primary challenges faced by teachers in inclusive classrooms are related to instructional strategies and media. Moreover, this study stands out for its focus on English language education for students with special needs in public schools, addressing a gap in previous research. It provides new insights into inclusive educational practices in a broader context, emphasizing the importance of understanding diverse classroom dynamics and meeting the needs of students with special needs in a general educational environment. Keywords: Student with special needs, private school, English teaching strategies